Efficiencyequity tradeoffs and the scope for resource reallocation in agricultural research: evidence from Nigeria - Alene, Arega D.; Manyong, Victor M.; Tollens, E.F.; Abele, S. (Wiley, 2009)
On the basis of projected economic and poverty impacts of alternative commodity research programs, this article assessed efficiency and equitytradeoffs and the scope for research resource reallocation in Nigeria. Given the importance of major food staples to both poor and nonpoorhouseholds in production and consumption, introducing a poverty dimension revealed no significant shift in priorities compared with those impliedby efficiency. The results showed that neither the additional benefits to the poor nor the foregone benefits to society are significant from prioritizingresearch according to equity—relative to efficiency—criteria. As current priorities are supported by neither efficiency nor equity criteria, however,there is considerable scope for maximizing research benefits to the poor through informed reallocation of research resources. The article concludeswith a discussion of the patterns of resource reallocations implied by efficiency and equity criteria.